2022
DOI: 10.3389/fcvm.2022.1013490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on vascular function in hypertension patients: A meta-analysis of randomized controlled trials

Abstract: ObjectiveThe purpose of this study was to systematically evaluate the effect of exercise on vascular function in patients with pre- and hypertension.MethodsA systematic review of articles retrieved via the PubMed, Embase, EBSCO, and Web of Science databases was conducted. All the randomized controlled trials published between the establishment of the databases and October 2022 were included. Studies that evaluated the effects of exercise intervention on vascular function in patients with pre- and hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 102 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…Numerous advantages of physical exercise for cardiovascular health include decreasing blood pressure, raising insulin sensitivity, improving lipid profiles, reducing inflammation, and avoiding obesity [20] . Through processes such as lowered sympathetic tone, enhanced vascular endothelial function, and decreased arterial stiffness, exercise lowers blood pressure [21] . While reducing LDL and triglycerides, exercise can increase HDL cholesterol [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous advantages of physical exercise for cardiovascular health include decreasing blood pressure, raising insulin sensitivity, improving lipid profiles, reducing inflammation, and avoiding obesity [20] . Through processes such as lowered sympathetic tone, enhanced vascular endothelial function, and decreased arterial stiffness, exercise lowers blood pressure [21] . While reducing LDL and triglycerides, exercise can increase HDL cholesterol [22] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Pedralli, it was observed that various aerobic exercise, resistance exercise, and combined exercise improve significantly in the flow‐mediated dilation (FMD) indices among hypertensive patients 67 . A total of 571 participants in nine studies were enrolled in a meta‐analysis to evaluate the effects of exercise on FMD in hypertensive patients, it showed that exercise significantly improved FMD in patients compared to controls 18 . Results from another meta‐analysis of endothelial function in diabetic patients found that exercise training improved FMD in type 2 diabetic patients by 1.77% overall 65 .…”
Section: Discussionmentioning
confidence: 99%
“… 17 A meta‐analysis conducted by Zhou noted that exercise intervention significantly improved systolic and diastolic blood pressure and FMD in hypertensive patients, but was ineffective in reducing PWV. 18 Some other studies have discovered that exercise does not significantly improve endothelial function in hypertension, possibly because of different exercise styles and exercise intensities. 19 , 20 In addition, no consistent conclusions have been drawn given the small sample sizes and varying exercise intervention programs of previous studies in the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, AT and RT were found to reduce 24-hour systolic BP, whereas CT did not have the same effect. Only two randomized controlled trials have investigated the persistent impact of various exercise modalities on endothelial function in individuals diagnosed with arterial hypertension [45]. These studies provide valuable clinical insights into combating endothelial dysfunction as a significant cardiovascular risk factor among patients about 40 years with prehypertension or arterial hypertension.…”
Section: Regular Physical Exercisesmentioning
confidence: 99%